2021
DOI: 10.3390/su13136993
|View full text |Cite
|
Sign up to set email alerts
|

Channel Depth or Consistency? A Study on Establishing a Sustainable Omnichannel Strategy for Fashion Department Store Retailers

Abstract: In recent years, fashion department stores have struggled to sustain their foothold in the competitive market due to changing consumer behavior as well as technological advancement. This study aimed to examine customers’ perspectives on the shopping channels of omnichannel fashion department stores. The analysis was based on data from 552 customers who shopped at U.S. omnichannel fashion department stores. Confirmatory factor analysis and structural equation modeling were utilized to analyze the hypothesized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The availability of multiple customer service channels was the most common feature offered by luxury segment companies worldwide, which shows that these companies value the Consistency dimension to provide a fluid experience for their customers. According to Kopot and Cude (2021), consistency in product offerings and information is crucial for customers when purchasing. However, Lee 2019) claim that one of the significant difficulties for many companies is that sometimes the consistency between different channels is not fulfilled.…”
Section: Adapted Model From Shi Et Al (2020)mentioning
confidence: 99%
“…The availability of multiple customer service channels was the most common feature offered by luxury segment companies worldwide, which shows that these companies value the Consistency dimension to provide a fluid experience for their customers. According to Kopot and Cude (2021), consistency in product offerings and information is crucial for customers when purchasing. However, Lee 2019) claim that one of the significant difficulties for many companies is that sometimes the consistency between different channels is not fulfilled.…”
Section: Adapted Model From Shi Et Al (2020)mentioning
confidence: 99%
“…The concept of channel consistency has been well acknowledged, and researchers have suggested that customers are likely to move across multiple retail channels and to expect a consistent shopping journey [23,27]. Consistent omni-channel shopping provides customers with options to purchase at any time and place, thus inducing positive outcomes such as customer loyalty [38], satisfaction [39], attitudes to retailers [40], and consumption [29].…”
Section: Omni-channel Consistencymentioning
confidence: 99%
“…Previous research on omni-channel consistency often focuses on two dimensions, content and process consistency [41]. The prior refers to "the consistency of information features across different channels" [29], while the latter represents "the degree of consistency of relevant and comparable process attributes across channels" [30]. Although some extant literature has implied that omni-channel retailers ought to provide consistent customer experience, there has been a limited number of studies on omni-channel customer experience consistency [28].…”
Section: Omni-channel Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…Even before the COVID-19 pandemic, several department stores, such as J.C. Penney, Sears, Wilson's, among others, have faced significant survival challenges in recent years because of the rise of online shopping (Ford et al , 2021; Tokosh, 2019). This has prompted managers and researchers to ask how to execute effective online strategies (Jones and Livingstone, 2018; Kopot and Cude, 2021; Zhang and Lin, 2014). Websites are an essential medium for interacting with consumers (Alonso‐Dos‐Santos et al , 2019; Chiou et al , 2011; Rosenbaum and Russell-Bennett, 2021; Stepchenkova et al , 2010).…”
Section: Introductionmentioning
confidence: 99%